Audit Informasi pada Unit Layanan Book Carrier Perpustakaan Bank Pustaka - Fauziah, Kiki (UI Scholars Hub, 2020)
This article discusses information audit process in the book carrier service unit of Bank Pustaka Library. The purpose of this study was to see flow of information on the book carrier services, to identify effectiveness of work instructions for book carrier services and to identify information needs in the book carrier service unit. This research used a qualitative approach with a case study method. The data collection was conducted by interview, observation, and document analysis. The study results found that there was miscommunication between the coordinator and staff in providing work instructions, work instructions of the book carrier service were not delivered to the book carrier guard staff, the selection of collections contained in the book carrier cart was not adjusted yet to the information needs of the users in the work unit to be visited, and there was duplication related to the collections in the book carrier cart every week.